2020
DOI: 10.21203/rs.3.rs-21694/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outcomes of and factors associated with partner notification and HIV testing in Northeastern Tanzania.

Abstract: Background: There is growing evidence of high effectiveness of partner notification (PN) in reaching previously undiagnosed sexual partners. As a result, there is increasing implementation of PN in sub-Saharan Africa. Tanzania, like other countries in the region, has recently expanded PN in HIV testing services. However, this approach is unlikely to yield the expected results if not well implemented. This study aimed to identify gaps and provide recommendations to improve routine implementation of PN in Tanzan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…Other studies have reported low uptake of HIV counseling and testing services among married couples (28, 29). This nding was contrary to what Lyamuya and colleagues found that married participants in their study were 410 times more likely to take up APN than those who were not (30). Relatedly, widowhood had no signi cant association with uptake of APN, which is similar to ndings by Lyamulya and colleagues (30).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Other studies have reported low uptake of HIV counseling and testing services among married couples (28, 29). This nding was contrary to what Lyamuya and colleagues found that married participants in their study were 410 times more likely to take up APN than those who were not (30). Relatedly, widowhood had no signi cant association with uptake of APN, which is similar to ndings by Lyamulya and colleagues (30).…”
Section: Discussioncontrasting
confidence: 80%
“…Of the 125 study participants, 41 (32.8%) took up APN. The majority (69%) were females, and the median (IQR) age was 29.5 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) years. Only 48.6% were married, 78% had good adherence to ART, and 80% had received at least three adherence counseling sessions before they were introduced to the APN.…”
Section: Characteristics Of Study Participantsmentioning
confidence: 99%
“…The proportion was that a similar to a study carried out in the Tanzania (Plotkin et al, 2018) on the study on the outcomes of men and women on partner notification indicated that 63.4% of the male partners were successfully referred and 49.8% of the female partners were referred. However, the participation rates were low compared to a study in Mozambique where uptake of assisted partner notification was 85% where the index patients gave community health workers permission to contact their partners (Myers et al, 2016).Similarly, according a study in Tanzania on outcomes and factors associated with partner notification, 85% of the HIV care clients consented to participate in partner notification (Lyamuya et al, 2020). Assisted partner notification was established to be safe, acceptable and effective (Myers et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…22 Partner notification also needs to be delivered in a differentiated way, just as the delivery of HIV testing and ART. 23 The most commonly known differentiated PN methods include passive referral, contract referral, and provider referral, and some studies incorporated other interventions such as providing HIV self-testing or MSM-serving community-based organizations outreach. 3,24 Our results extend the idea of differentiated HIV PS by providing different combinations of interventions to index clients based on the evaluation of notification risks, relationship status, and other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Different models of differentiated care have been developed for PLHIV based on clinical characteristics, subpopulation, and client context 22 . Partner notification also needs to be delivered in a differentiated way, just as the delivery of HIV testing and ART 23 . The most commonly known differentiated PN methods include passive referral, contract referral, and provider referral, and some studies incorporated other interventions such as providing HIV self-testing or MSM-serving community-based organizations outreach 3,24 .…”
Section: Discussionmentioning
confidence: 99%